1993
DOI: 10.1111/j.1464-410x.1993.tb16030.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tissue Factor Levels in Prostatic Carcinoma: A Potential. Marker of Metastatic Spread ?

Abstract: Recent investigations have suggested that levels of urinary tissue factor (UTF) may be elevated in some forms of cancer. We have determined UTF levels in healthy controls, patients presenting for surgery with benign prostatic hypertrophy (BPH) and untreated prostate cancer. Patients undergoing check cystoscopy, who were free of recurrent bladder cancer, and a cohort of men with bone scan positive prostate cancer recently treated by androgen ablation were also studied. UTF levels were higher in patients with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
2
20
1
Order By: Relevance
“…This result confirms other reports 16 and is also consistent with our finding that uTF activity is increased with tumor grade or stage.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This result confirms other reports 16 and is also consistent with our finding that uTF activity is increased with tumor grade or stage.…”
Section: Discussionsupporting
confidence: 83%
“…13,14 Previous studies have shown that uTF is increased in patients with cancer and inflammatory bowel diseases, [13][14][15][16] although unpublished studies by other workers failed to confirm this finding. Recently, we described a highly standardized assay for measuring uTF activity, with a coefficient of variation (CV)<10%.…”
contrasting
confidence: 36%
See 3 more Smart Citations